The power to destroy : a study of the British Tax system - Myddelton, David Roderic (London : Johnson, 1969)
This book is on taxation which consist of direct seizure of private money or property by the State, backed by the threat of force Confiscation ("appropriation to the State treasury" "legal robbery with sanction of ruling power") implies neither total seizure as is commonly thought, nor any element of penalty.
Includes index.
Includes bibliographical references: p. 229-236.
osa 25/01/2019
Loans
Keywords: Taxation